The growth response of rice (Oryza sativa L. var. FARO 44) in vitro after inoculation with bacterial isolates from a typical ferruginous ultisol - Ibrahim, Musa Saheed (2023)
16S rRNA gene sequencing identified the isolates as: isolate BCAC2= Bacillus cereus strain GGBSU-1, isolate BCAF1= Proteus mirabilis strain TL14-1 and isolate EMBF2= Klebsiella variicola strain AUH-KAM-9. Significant improvement in rice germination, morphology, physiology and biomass parameters in the bacteria-inoculated setups was observed compared to the control. Germination percentage after 4 days was 100 % in the inoculated rice germinants compared to 65% in the control (NiS). Similarly, inoculation with the test isolates enhanced water-use efficiency by over 40%. The rice seedlings inoculated with Bacillus cereus strain GGBSU-1 (BiS) showed no signs of chlorosis and necrosis throughout the study period as against those inoculated with Proteus mirabilis strain TL14-1 (PiS) and Klebsiella variicola strain AUH-KAM-9 (KiS). Significant increase in chlorophyll-a, chlorophyll-b and alpha amylase was observed in the rice seedlings inoculated with BiS as against the NiS.